Impact of sex, race, and social determinants of health on neonatal outcomes - Alur, Pradeep; Holla, Ira; Hussain, Naveed (Frontiers in Pediatrics, 2024)
Despite the global improvements in neonatal outcomes, mortality and morbidity rates among preterm infants are still unacceptably high. Therefore, it is crucial to thoroughly analyze the factors that affect these outcomes, including sex, race, and social determinants of health. By comprehending the influence of these factors, we can work towards reducing their impact and enhancing the quality of neonatal care. This review will summarize the available evidence on sex differences, racial differences, and social determinants of health related to neonates. This review will discuss sex differences in neonatal outcomes in part I and racial differences with social determinants of health in part II. Research has shown that sex differences begin to manifest in the early part of the pregnancy. Hence, we will explore this topic under two main categories: 1) Antenatal and 2) Postnatal sex differences. We will also discuss long-term outcome differences wherever the evidence is available. Multiple factors determine health outcomes during pregnancy and the newborn period. Apart from the genetic, biological, and sex-based differences that influence fetal and neonatal outcomes, racial and social factors influence the health and well-being of developing humans. Race categorizes humans based on shared physical or social qualities into groups generally considered distinct within a given society.1 Social determinants of health (SDOH) are the non-medical factors that influence health outcomes. These factors can include a person's living conditions, access to healthy food, education, employment status, income level, and social support. Understanding these factors is essential in developing strategies to improve overall health outcomes in communities.